2018
DOI: 10.1177/1066896918755008
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Additional Tissue Sections in Surgical Pathology

Abstract: AS per case ranged widely; their diagnostic yield was low; they were highest in urinary bladder specimens, in malignant and particularly neoadjuvant-treated lesions. Although lymph nodes were most heavily sampled, most AS were from masses. Resident dissection did not increase AS and cost of AS was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…A recent study found upstaging of pT stage in 7 of 53 cases when the entire tumor bed was submitted. 28 In our study, 9.2% patients received neoadjuvant therapy. Among these 47.4% cases had concordant size compared with 56.8% cases, where the patients did not receive neoadjuvant therapy; however, this difference was not statistically significant (P = .26).…”
Section: Discussionmentioning
confidence: 63%
“…A recent study found upstaging of pT stage in 7 of 53 cases when the entire tumor bed was submitted. 28 In our study, 9.2% patients received neoadjuvant therapy. Among these 47.4% cases had concordant size compared with 56.8% cases, where the patients did not receive neoadjuvant therapy; however, this difference was not statistically significant (P = .26).…”
Section: Discussionmentioning
confidence: 63%
“…The main core of diagnosis of UPS is to exclude other malignant tumors that display similar morphological findings such as malignant melanomas, sarcomatoid carcinomas, anaplastic lymphomas, sarcomatoid mesotheliomas, or other sarcomas (e.g., dedifferentiated liposarcoma and pleomorphic rhabdomyosarcoma, etc.). Therefore, it is a diagnosis of exclusion, which requires careful examination of tissue and generous sampling of the specimen to stablish a correct diagnosis 12. This diagnosis should not be made definitively on a biopsy specimen, because the entire mass is not present in the biopsy materials.…”
Section: Discussionmentioning
confidence: 99%
“…28,47-49 Finally, it is important to emphasize that thorough tissue sampling is extremely invaluable in reaching the correct diagnosis. 50,51…”
Section: Discussionmentioning
confidence: 99%